2020
DOI: 10.1002/cbin.11303
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle‐derived circ_SLC19A1 promotes prostate cancer cell growth and invasion through the miR‐497/septin 2 pathway

Abstract: The occurrence and development of prostate cancer (PCa) is complex, and the related mechanism is not fully understood. Current studies have found that extracellular vesicles (EVs) and circular RNAs (circRNAs) have important functions in various tumours and other diseases. In this study, the detection of circRNAs in PCa showed that circ_SLC19A1 was increased in PCa cells and their secreted EVs. EVs with high expression of circ_SLC19A1 could be taken up by PCa cells, which promoted cell proliferation and invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 24 publications
3
27
1
Order By: Relevance
“…Besides, Zheng's study showed that high circSLC19A1 expression was associated with promotion of PCa cell migration and invasion. 15 Consistent with this, we found that forced decrease of circSLC19A1 expression inhibited PCa cell proliferation, colony formation, migration and invasion, reaffirming the oncogenic role of circSLC19A1.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Besides, Zheng's study showed that high circSLC19A1 expression was associated with promotion of PCa cell migration and invasion. 15 Consistent with this, we found that forced decrease of circSLC19A1 expression inhibited PCa cell proliferation, colony formation, migration and invasion, reaffirming the oncogenic role of circSLC19A1.…”
Section: Discussionsupporting
confidence: 86%
“…According to one previous study by Zheng, circSLC19A1 was highexpressed in extracellular vesicles secreted by PCa cells. 15 Similarly, we found circSLC19A1 expression was up-regulated in PCa tissues and cell lines. To further confirm the result, DU145 and PC3 cells which exhibited relatively higher circSLC19A1 expression were subjected to RNase R digestion.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…While the mechanisms that mediate the biological effects of EVs on their cellular targets remain poorly known, it is clear that EVs are implicated in most, if not all, physiopathological processes, including signal transduction, cell growth, and differentiation, metabolic regulation, embryofetal development, organogenesis, tissue homeostasis and repair/regeneration, antigen presentation and immune response, ageing, pathogen-host interactions, carcinogenesis, tumor invasion/metastasis, cardiovascular dysfunction, etc. [9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The EV cargo, packaged within relatively stable membrane-bound structures, is sheltered from degradation by the extracellular enzymes present in biological fluids, and may therefore maintain biological stability over comparatively long periods of time [38].…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%